1974
DOI: 10.1021/ja00832a005
|View full text |Cite
|
Sign up to set email alerts
|

Heterobihalide ions. Nuclear magnetic resonance spectroscopy of strong hydrogen bonds

Abstract: The hydrogen and fluorine nmr spectra of the fluorine bihalide ions FHX~( X = F, Cl, Br, and I) complete our study of the ten bihalide ions in aprotic solvents. The H-F coupling constant has been resolved in all four fluorine bihalides. Exchange of fluorine is slow; exchange of the other halogens is fast on the nmr time scale. The formation and interconversion equilibria may be adequately interpreted by assuming quantitative hydrogen transfer to the most basic (the smallest) halide ion in the system. Consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
28
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 12 publications
7
28
0
Order By: Relevance
“…This is not without precedent for fluorides since it has been reported that crystals of KF(CH,CO,H), grow from KF-CH,CO,H solutions (1). All of the disolvates are soluble in common polar aprotic (2,4,7). The commonly observed effect on the H-bonding proton resonance on going from the self-associated electron acceptor to the anionic complex is a deshielding (downfield shift) one which is usually assumed to reflect an increase in strength of the H-bond.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not without precedent for fluorides since it has been reported that crystals of KF(CH,CO,H), grow from KF-CH,CO,H solutions (1). All of the disolvates are soluble in common polar aprotic (2,4,7). The commonly observed effect on the H-bonding proton resonance on going from the self-associated electron acceptor to the anionic complex is a deshielding (downfield shift) one which is usually assumed to reflect an increase in strength of the H-bond.…”
Section: Resultsmentioning
confidence: 99%
“…It would seem, therefore, that while the intermolecular association of this oxime is disrupted by the highly localised electron density of the fluoride anion, the intramolecular association remains intact (eq. [4]). …”
Section: Infrared Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…In Figure 1 (Figure 1b) and 19 F NMR (Figure 1c). For the former sample b was used, containing a higher total concentration of the complex and a smaller excess (7-fold) of the base.…”
Section: Abstract In Russianmentioning
confidence: 96%
“…[17][18][19][20] In additional experiments with TBAF trihydrate a t 77 "C (2 torr) we noted not only mass loss as a function of time but also changes in physical appearance as well. For example, when placed at 77 OC, the crystalline trihydrate immediately melted to a colorless liquid from which bubbles evolved.…”
Section: Results a N D Discussionmentioning
confidence: 68%